Quality Analysis of the West Papua Tribune Website With the Webqual 4.0 Method: Evaluation of User Satisfaction - Listia Rachmayani; Marlinda Sanglise; Julius P.P. Naibaho (Universitas Islam Raden Rahmat, Malang, 2025)
The development of information technology has driven changes in news consumption, with online media becoming the main source of information for the public. Tribun News West Papua, as one of the news portals, has an important role in presenting fast and relevant news. However, website quality affects user satisfaction, so an evaluation of Usability, Information Quality, and Service Interaction Quality aspects is needed. This study aims to analyze the quality of the Tribun News West Papua website using the WebQual 4.0 method and see the effect of these three variables on user satisfaction. The quantitative approach used 134 respondents and the data was analyzed using PLS-SEM through SmartPLS 4.0. The results showed that Usability has no significant effect on user satisfaction, while Information Quality and Service Interaction Quality have a positive and significant effect. Service Interaction Quality has the most dominant influence where service responsiveness and ease of interaction are the main aspects in increasing user satisfaction. This research shows that increasing user satisfaction can be achieved by keeping the news current and improving service interaction features, such as a more responsive commenting system.